Grievable lives? Death by opioid overdose in Australian newspaper coverage - Fraser, Suzanne; Farrugia, Adrian; Dwyer, Robyn (Elsevier BV, 2018)
Opioid overdose deaths are increasing in Australia and around the world. Despite this, measures aimed at reducing these deaths such as safe injecting facilities and take-home naloxone continue to face obstacles to uptake. The reasons for this are manifold, but a key contributor is public discourse on opioid consumption and overdose. In this article we explore this public discourse using Judith Butler's work on ‘grievable lives’. The article analyses mainstream newspaper coverage of opioid overdose in Australia to map key articulations of overdose and to consider how public understandings of overdose are shaped. It then goes on to consider ways these understandings might be reshaped, looking at what have been called overdose ‘anti-memorials’ and a new website Livesofsubstance.org. In concluding we argue that until the lives of opioid consumers come to be considered grievable, the measures known to reduce overdose deaths may struggle to find public support.